A High Energy Density Aqueous Battery Achieved by Dual Dissolution/Deposition Reactions Separated in Acid‐Alkaline Electrolyte. Issue 12 (31st January 2020) - Liu, Chang; Chi, Xiaowei; Han, Qi; Liu, Yu
Abstract: Aqueous batteries are facing big challenges in the context of low working voltages and energy density, which are dictated by the narrow electrochemical window of aqueous electrolytes and low specific capacities of traditional intercalation‐type electrodes, even though they usually represent high safety, low cost, and simple maintenance. For the first time, this work demonstrates a record high‐energy‐density (1503 Wh kg −1 calculated from the cathode active material) aqueous battery system that derives from a novel electrolyte design to expand the electrochemical window of electrolyte to 3 V and two high‐specific‐capacity electrode reactions. An acid‐alkaline dual electrolyte separated by an ion‐selective membrane enables two dissolution/deposition electrode redox reactions of MnO2 /Mn 2+ and Zn/Zn(OH)4 2− with theoretical specific capacities of 616 and 820 mAh g −1, respectively. The newly proposed Zn–Mn 2+ aqueous battery shows a high Coulombic efficiency of 98.4% and cycling stability of 97.5% of discharge capacity retention for 1500 cycles. Furthermore, in the flow battery based on Zn–Mn 2+ pairs, more excellent stability of 99.5% of discharge capacity retention for 6000 cycles is achieved due to greatly improved reversibility of the Zn anode. This work provides a new path for the development of novel aqueous batteries with high voltage and energy density. Abstract : An ultrahigh energy density (1503 Wh kg −1 based on the cathode active material) aqueous Zn–Mn 2+ battery is designed by coupling an acid‐alkaline dual electrolyte and dual dissolution/deposition reactions of both the anode and cathode. The new Zn–Mn 2+ batteries show high Coulombic efficiency and excellent cycling stability.